Classification of FTIR Spectra of Olive Oil with Features of Variational Mode Decomposition and Wavelet Transform - Karaaslan, Omer Faruk; Bilgin, Gokhan (IEEE, 2019)
Nowadays, it becomes important to determine the chemical structure without damaging the samples. As a result of the use of infrared, the spectras are obtained both quickly and without any special sample preparation process, and they contain specific characteristics. In this study, features of Fourier Transform Infrared spectra acquired from olive oil samples are extracted by Wavelet Transform (WT) and Variational Mode Decomposition (VMD) that does not require a main function.Afterwards, these attributes are classified in comparison by using the powerful classifiers, support vector machines (SVM) and random forests (RF). Experimental studies have shown that the features obtained by two proposed methods increase the classification performance.
Keywords: Fourier transform infrared spectroscopy (FTIR); wavelet transform; variational mode decomposition; support vector machinesi; random forests; classification; GEOGRAPHICAL ORIGIN; SPECTROSCOPY; Engineering; Telecommunications